A EDUCAÇÃO PARA AS RELAÇÕES ÉTNICO-RACIAIS NA FORMAÇÃO CONTINUADA DOS PROFESSORES DA BAIXADA SANTISTA: DEZ ANOS APÓS A INSTITUCIONALIZAÇÃO DA LEI 10.639/03 - Ramos, Anália Cristina Pereira (2015)
The current work discuss the implementation of The Federal Law 10639/03, in the state public school in Baixada Santista-SP region, after ten years of the Law´s institucionalization. Investigated about the continuous formation of the docents, relationshiped it with the way, in this pedagogic praxis, the docents has come inserting the contents of African History and Culture and the Afro-brazilians history and culture that became obligatory by the law. The research was realized with the docents of History, Portuguese Languages and Arts, that teach for the High school of the state public net in Guarujá, Santos, Cubatão and Bertioga and it was contextualized with the local reality and the permanent formation for the Educational of Ethnic-Racial Relations. It was taking in consider the institutionals or no institutional knowledges, involving in the reflexive way, in the sense of bring the methods of teaching as the multiculturalism that might to ensure that all the ethnics that composed the Brazilian people, rising its self- steaming and valorization of the cultural aspects, aiming to spirit of citizens and alterity. The process of qualitative research involved the bibliographic and documental analyses, application of: action research, semi-structured questionnaire by internet, interviews and analyses of pedagogic experiences. Empirics results shows that in this ten years, except any successful experiences, the major of docents considered they has got a few or amount anything information about the Law 10639/03. It is the same about the teacher´s skill building required to deepen the discussions and the contents that its implicates. This fact indicates the need greater in teacher education, from the government and major political incentive for teachers to encourage them to pursue continuing education and adoption of reflexives practices and critical focusing on educations and ethnic-racial relations, allying the need for a multi-ethnic and multicultural contemporary society.